Does patient load affect clinical outcome of burn patients in specialized centers? An analysis of the German Burn Registry. Issue 3 (May 2022) - Schiefer, JL; Bagheri, M.; Fuchs, PC; Lefering, R.; Rennekampff, HO; Vogt, PM; the German Burn Registry,; Busche, MN
Highlights: Burn center volume does not affect mortality in Germany. Patients treated in large volume burn centers received more surgeries. Patients treated in large volume burn centers showed an increased length of hospital stay. Abstract: Hospital volume has been identified as an independent outcome parameter for a number of medical fields and surgical procedures, and there is a tendency to increase required patient numbers for center verification. However, the existing literature does not support a clear correlation between patient load and clinical outcome in adult burn care and recent data from Germany does not exist. We therefore evaluated the effect of patient volume in German burn centers on clinical outcome. Patient data was extracted from the German Burn Registry from 2015 to 2018. For better inter-center comparability, solely burn patients with a TBSA ≥ 10% were included. Mortality, number of surgeries and length of stay (LOS) were evaluated with respect to burn center patient volume. Burn center volume was divided into two and three groups. A total of 2718 patients with a TBSA ≥ 10% were admitted to the participating 17 burn centers. Independent from the division of patient data into either 2 or 3 groups, the TBSA and ABSI score-related severity of burn injuries were comparable between groups. There was no significant difference in mortality due to center size. Nevertheless, patients treated in large volume burn centers showed a significantly increased LOS (+4.5 days, [1.9–7.2] CI, p = 0.001) and required significantly more surgeries (+0.5 surgeries [0.2–0.8] CI, p = 0.002) when compared to the small volume centers. A similar phenomenon regarding mortality and LOS (p 0.001) was observed after dividing the centers into two groups. Interestingly a division into three groups showed significant differences with the best outcome for patients in medium-volume centers. Nevertheless, mortality did not differ significantly. Therefore, our data demonstrates that in contrast to many other medical fields, outcome and mortality are not automatically improved in burn care by simply increasing the patient load, at least in centers treating 20–100 BICU patients/year.